Place, nations, generations, beings 200 years of Indigenous North American art - McCleary, Katherine Nova (Yale University Art Gallery, 2019)
"This important publication is the first from the Yale University Art Gallery dedicated to Indigenous North American art. Accompanying a student-curated exhibition, it marks a milestone in the collection, display, and interpretation of Native American art at Yale and seeks to expand the dialogue surrounding the University's relationship with Indigenous peoples and their arts. The catalogue features an introduction by the curators that surveys the history of Indigenous art on campus and outlines the methodology used while researching and mounting the exhibition; a discussion of Yale's Native American Cultural Center; and a preface by the Medicine Woman and Tribal Historian of the Mohegan Nation. Also included are images of nearly 100 works-basketry, beadwork, drawings, photography, pottery, textiles, and wood carving, from the early 1800s to the present day-drawn from the collections of the Gallery, the Yale Peabody Museum of Natural History, and the Beinecke Rare Book and Manuscript Library. The objects are grouped into four sections, each introduced with a short essay, that center on the themes in the book's title. Together, these texts and artworks seek to amplify Indigenous voices and experiences, charting a course for future collaborations"--Publisher's description